2018
DOI: 10.1080/17470218.2017.1281321
|View full text |Cite
|
Sign up to set email alerts
|

The dual reading of general conditionals: The influence of abstract versus concrete contexts

Abstract: A current main issue on conditionals is whether the meaning of general conditionals (e.g., If a card is red, then it is round) is deterministic (exceptionless) or probabilistic (exception-tolerating). In order to resolve the issue, two experiments examined the influence of conditional contexts (with vs. without frequency information of truth table cases) on the reading of general conditionals. Experiment 1 examined the direct reading of general conditionals in the possibility judgment task. Experiment 2 examin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1

Relationship

6
3

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 35 publications
(76 reference statements)
2
7
1
Order By: Relevance
“…We found that only the pq possibility is necessary for a true conditional, and the p¬q possibility is incompatible with the true conditional. This incompatibility is different from, but not in conflict with the previous finding that in set tasks with the manipulation of probability, people prefer the probabilistic reading (tolerating few exceptions) of general conditionals, in which p¬q is possible (Evans, Handley, & Over, 2003;Evans & Over, 2004;Geiger, & Oberauer, 2007;Oberauer, Geiger, Fischer, & Weidenfeld, 2007;Wang & Yao, 2018). In the present set tasks, different cases in a set are equiprobable.…”
Section: Relation To Existing Researchcontrasting
confidence: 87%
See 1 more Smart Citation
“…We found that only the pq possibility is necessary for a true conditional, and the p¬q possibility is incompatible with the true conditional. This incompatibility is different from, but not in conflict with the previous finding that in set tasks with the manipulation of probability, people prefer the probabilistic reading (tolerating few exceptions) of general conditionals, in which p¬q is possible (Evans, Handley, & Over, 2003;Evans & Over, 2004;Geiger, & Oberauer, 2007;Oberauer, Geiger, Fischer, & Weidenfeld, 2007;Wang & Yao, 2018). In the present set tasks, different cases in a set are equiprobable.…”
Section: Relation To Existing Researchcontrasting
confidence: 87%
“…In set tasks about truth judgments of conditionals, some previous studies investigated whether the meaning of general conditionals (e.g., If a card is red, then it is round) is deterministic (exceptionless) or probabilistic (exception-tolerating) (Evans, Handley, & Over, 2003;Evans & Over, 2004;Fugard, Pfeifer, Mayerhofer, & Kleiter, 2011;Geiger, & Oberauer, 2007;Goodwin, 2014;Oaksford & Chater, 2009;Oaksford, Chater, & Larkin, 2000;Oberauer, Geiger, Fischer, & Weidenfeld, 2007;Oberauer & Wilhelm, 2003;Over & Cruz, 2018;Wang & Yao, 2018). In these studies, frequency information of the four truth table cases and P(q|p) were manipulated to examine whether participants tolerated exceptions to conditionals and whether truth judgments varied with P(q|p).…”
Section: Existing Empirical Studies and Their Limitationsmentioning
confidence: 99%
“…The semantic violation interpretation of negated general disjunctions parallels the previous 34 finding that most participants judged a general conditional, if p then not q (e. g., if a card is round then it is red), false in a set containing p¬q cases where different cases were equiprobable by default (Wang & Yao, 2018). That the general conditional is false is equivalent to that the general conditional is not true, that is, the negation of the general conditional.…”
Section: Discussionsupporting
confidence: 70%
“…In concrete contexts with frequency information of the four cases, p¬q should be possible. This difference is suggested by the previous finding that people generally show the deterministic reading of conditionals without frequency information (e. g, if a card is round then it is red), but the probabilistic reading (tolerating a few exceptions) of conditionals with frequency information (Wang & Yao, 2018). Thus, for the instance modal question about a basic conditional without frequency information, the true conditional implies that pq is possible for the instance, and irrelevant ¬pq and ¬p¬q are also possible (this may be due to that logically they are not incompatible with the true conditional), but p¬q is impossible (Handley, Evans, & Thompson, 2006, p 565).…”
Section: Introductionmentioning
confidence: 90%